Kant on the Relations between Church and State: An Introduction to the Special Edition (Diametros, 2020)
This introduction is divided into two parts. First, drawing on Paul Guyer’s suggestion that we should turn to Kant to reinvestigate the foundations of religious liberty, I outline Kant’s views on the relations between the ethical (‘church’) and the political (‘state’) community, as presented in Part Three of the Religion within the Boundaries of Mere Reason, focusing in particular on his arguments for separation between religion and the state. Examining critically the idea to employ Kant in contemporary debates, I claim that Kant’s account of pure moral faith and the church as its ‘vehicle’ may pose difficulties for any argument for religious liberty that appeals to his thought. For Kant is better equipped to offer resources to overcome rather than to accommodate the fact of so-called “moral pluralism,” i.e. the condition in which the principle of religious liberty can find its application. In the second part, I summarise the arguments of the authors who contribute to this volume: D. Jakušić, W. Kozyra, S. Lo Re, G.E. Michalson Jr., and S.R. Palmquist.
Keywords: Kant; religious liberty; moral pluralism; pure moral faith; ethical community; ecclesiastical faith; church-state relations; secularisation